The Uneven and Unsure Playing Field for Competition Damages' Claims in the EU: Shortcomings and Failures of Directive 2014/104/EU and Its Implementation - Marcos, Francisco (Springer Nature, 2021)
This paper examines the impact that Directive 2014/104/EU in the rules governing private damages claims for competition infringements and in the ensuing latest litigation in some Member States. Not more than three years have passed since the Directive was implemented, but there are already signs that instead of facilitating damages claims, the rules established do not facilitate claims; to the contrary, some of them may unnecessarily complicate the prospects for compensation of competition infringements’ victims. Initial assessments of the Directive already pointed out its biases and shortcomings and the complexities introduced by some of its provisions. From the start it has been clear that the partial harmonization sought by the Directive would leave room for relevant divergences among Member States due to the principle of national autonomy. Limited harmonization and the leeway on the rules governing jurisdiction provide ample leeway for plaintiffs to choose where to file their claims. The implementation of the Directive has only confirmed the initial appraisal. In many of the relevant issues covered by the Directive, the jigsaw of national rules has been further thickened with another layer complexities and uncertainties (f.e., contribution rules among infringers, indirect purchasers-passing on; access to evidence and disclosure). Doubts about the temporal application regime of the Directive have not helped, and it will take time to resolve them. More importantly, although some rules are introduced for the quantification of harm (and mainly for cartel infringements), they seem far for providing a helpful solution to national courts in practice. It may be too early to convict the solutions introduced by the Directive, but the ongoing cases in Member states already show that the outlook for damages has become far more uncertain and tortuous. Following the caselaw of the EUCJ, the Damages Directive has further encroached the national autonomy of Member States, but still too much is left to be ironed out using the principle of effectiveness. For that meager outcome, it can be question.
Keywords: Private Enforcement; Competition Law; Damages; Compensation; Directive 2014/104/EU; Harmonization; Principle of effectiveness; Principle of national autonomy; 56 Ciencias Jurídicas y Derecho; ODS 9 - Industria, innovación e infraestructura